2016
DOI: 10.1111/cen.13009
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of phenotype and genotype of congenital isolated hypogonadotropic hypogonadism in Asian Indians

Abstract: In our cohort, 60% were KS with majority of males and a severe reproductive phenotype as against nIHH. Contribution of the genetic burden for the five genes studied was 15·5%. RSV p.C279Y in GNRHR may have a founder effect originating from south Asia. This study provides a model for molecular and phenotypic representation of Asian Indian subjects with IHH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Patients with KS also had a higher percentage of associated developmental anomalies ( Table 2). Our data regarding the sensorineural hearing loss, which was present only in PPO groups and with a slightly higher percentage in patients with KS, were partially discordant with previous literature, reporting the presence of high percentage of hearing loss in patients with KS (25,26) and a total absence in nIHH (24). More importantly, the renal anomalies were only present in PPO groups and particularly in the male patients with KS.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Patients with KS also had a higher percentage of associated developmental anomalies ( Table 2). Our data regarding the sensorineural hearing loss, which was present only in PPO groups and with a slightly higher percentage in patients with KS, were partially discordant with previous literature, reporting the presence of high percentage of hearing loss in patients with KS (25,26) and a total absence in nIHH (24). More importantly, the renal anomalies were only present in PPO groups and particularly in the male patients with KS.…”
Section: Discussionsupporting
confidence: 69%
“…Some authors (21,22,23) reported a similar prevalence of cryptorchidism between KS and nIHH groups. In our cohort, congenital micropenis was present only in PPO groups, as expected (10,24,25), but the prevalence of male genital tract anomalies, including micropenis and cryptorchidism (Table 3), was significantly higher in patients with KS, thus indicating a more severe intrauterine androgen deficiency in patients with KS. All together, these findings support the idea of an hormonal condition that is generally worse among patients with KS.…”
Section: Discussionsupporting
confidence: 68%
“…Using Sanger sequencing, we detected a novel, de novo FGFR1 variant in exon 11 replacing the glycine residue at amino acid position 487 with a cysteine (p.Gly487Cys). Notably, a missense variant changing this glycine residue to an aspartic acid (p.Gly487Asp) was previously reported in an individual with Hartsfield syndrome and an individual with olfactogenital (Kallmann; MIM#147950) syndrome, the co-occurrence of congenital hypogonadotropic hypogonadism and anosmia (Hong et al 2016;Nair et al 2016). We modeled this variant in silico to assess its effect on the protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an activating mutation was identified in a girl with idiopathic central precocious puberty, under the autosomal dominant inheritance pattern [20]. Furthermore, oligogenic models of CHH transmission were reported in combination with heterozygous mutations of the KISS1R gene [21][22][23].…”
Section: Discussionmentioning
confidence: 99%